A novel BRAF mutation in association with primary amelanotic melanoma with oral metastases. (7th January 2014) - Zalaudek, I.; Ciarrocchi, A.; Piana, S.; Argenziano, G.; Torricelli, F.; Sancisi, V.; Gandolfi, G.; Longo, C.; Moscarella, E.; Banzi, C.; Nicoli, D.
Abstract Background In the context of amelanotic melanoma, little is known on the genetic or molecular background that determines the onset of this peculiar phenotype of melanoma and its sites of metastatic spread. However, it appears that amelanotic melanomas frequently lack BRAF mutations. Objective To report the genetical analysis of one case amelanotic melanoma developing oral metastasis. Methods The BRAF mutational status of the primary lesion was assessed by both Sanger sequencing and pyrosequencing. Results Both methodologies showed changes in three nucleotides: C1796T; G1798A and T1799A. These mutations should result in a rare double aminoacid substitution in codons 599 and 600 of the BRAF protein (BRAF T599I/V600K). Conclusion This unusual mutation was associated with an uncommon clinical phenotype of the primary tumour and with an unusual site of metastatic spread. In the lack of comparable data, a potential association between the unusual mutation and clinical findings remains a matter of further studies.